The Implementation of Speaking and English Dormitory Program: A Case Study - Muhammad Ali Mas'ud (Language-Edu, 2020)
This research was aimed to investigate: (1) the objective of speaking and dormitory program, (2) the strategies used in both programs, and (3) the management of the programs in Smart International Language College. The research design used was descriptive case study with interview, observation, and documentation as the instruments. The data was analyzed by qualitative data analysis by Miles and Huberman (1994); data reduction, data display, and drawing conclusion. The researcher stayed in dormitory and joined the programs for two weeks. The finding showed that speaking and dormitory programs were done twice in a day. In preparation, the tutor must join “asistansi” by joining and observing the class for a month to feel the real class atmosphere. Then, it is a must to join “micro teaching” by teaching the Smart team including the director who being the students to get some evaluations. Both programs were evaluated as internal and external evaluation. Smart ILC had some uniqueness. Smart had its own standard time called WIS (Waktu Indonesia Smart). Also, Smart had test schedule called “Placement Test”. In the class, the different color was used in different function. There were black, red, blue, and green.